Cyclin-dependent kinase inhibitors in malignant hematopoiesis - Schirripa, Alessia; Sexl, Veronika; Kollmann, Karoline (Frontiers in Oncology, 2022)
The cell-cycle is a tightly orchestrated process where sequential steps guarantee cellular growth linked to a correct DNA replication. The entire cell division is controlled by cyclin-dependent kinases (CDKs). CDK activation is balanced by the activating cyclins and CDK inhibitors whose correct expression, accumulation and degradation schedule the time-flow through the cell cycle phases. Dysregulation of the cell cycle regulatory proteins causes the loss of a controlled cell division and is inevitably linked to neoplastic transformation. Due to their function as cell-cycle brakes, CDK inhibitors are considered as tumor suppressors. The CDK inhibitors p16INK4a and p15INK4b are among the most frequently altered genes in cancer, including hematopoietic malignancies. Aberrant cell cycle regulation in hematopoietic stem cells (HSCs) bears severe consequences on hematopoiesis and provokes hematological disorders with a broad array of symptoms. In this review, we focus on the importance and prevalence of deregulated CDK inhibitors in hematological malignancies.